2008
DOI: 10.1242/dev.020255
|View full text |Cite
|
Sign up to set email alerts
|

Direct interaction of AGL24 and SOC1 integrates flowering signals in Arabidopsis

Abstract: During the transition from vegetative to reproductive growth, the shoot meristem of flowering plants acquires the inflorescence identity to generate flowers rather than vegetative tissues. An important regulator that promotes the inflorescence identity in Arabidopsis is AGAMOUS-LIKE 24 (AGL24), a MADS-box transcription factor. Using a functional estradiol-inducible system in combination with microarray analysis, we identified AGL24-induced genes, including SUPPRESSOR OF OVEREXPRESSION OF CO 1 (SOC1), a floral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
259
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 318 publications
(275 citation statements)
references
References 37 publications
11
259
1
4
Order By: Relevance
“…In this respect, it is pertinent to make a conclusion that LFY may partly mediate the PKL regulation of flowering time control via chromatin modification. Interestingly, AGL24 and SOC1 regulate each other and act together to activate LFY transcription (Liu et al, 2008;Lee et al, 2008) while both AGL8/FUL and LFY are independent downstream targets of SPL3 in flowering time and meristem identity control (Yamaguchi et al, 2009). Both SOC1 and LFY are direct targets of AGL8/FUL that binds to a region 2.2 kb upstream to the ATG codon of the LFY gene (Balanza et al, 2014), overlapping with a previously identified region that is also bound by SOC1 (Lee et al, 2008).…”
Section: How Does Pkl Regulate Lfy Expression?mentioning
confidence: 94%
“…In this respect, it is pertinent to make a conclusion that LFY may partly mediate the PKL regulation of flowering time control via chromatin modification. Interestingly, AGL24 and SOC1 regulate each other and act together to activate LFY transcription (Liu et al, 2008;Lee et al, 2008) while both AGL8/FUL and LFY are independent downstream targets of SPL3 in flowering time and meristem identity control (Yamaguchi et al, 2009). Both SOC1 and LFY are direct targets of AGL8/FUL that binds to a region 2.2 kb upstream to the ATG codon of the LFY gene (Balanza et al, 2014), overlapping with a previously identified region that is also bound by SOC1 (Lee et al, 2008).…”
Section: How Does Pkl Regulate Lfy Expression?mentioning
confidence: 94%
“…NF-Y binding mediates the regulation of SOC1 by CO and GA. To test in vivo whether CO and GA signalling regulate SOC1 through NF-Y binding to the NFYBE in the SOC1 promoter, we used an established pSOC1:b-glucuronidase (GUS) construct in which the GUS reporter gene was driven by a 2-kb SOC1 promoter upstream of the translational start site 5 . Based on this construct, we further created a mutated reporter gene cassette containing the Mut1 version of the NFYBE, 5 0 -TTCAgtAAgACgATT-3 0 (Fig.…”
Section: Nf-y Subunitsmentioning
confidence: 99%
“…In Arabidopsis, the timing of this transition is controlled by a complex network of flowering genetic pathways in response to developmental cues and environmental signals 1 . The interactions among these flowering pathways regulate the expression of two floral pathway integrators, FLOWERING LOCUS T (FT) and SUPPRESOR OF OVEREXPRESSION OF CONSTANS 1 (SOC1), which in turn activate the genes involved in the formation of floral meristems [2][3][4][5] . The major flowering pathways include photoperiod and gibberellin (GA) pathways that promote flowering in response to seasonal changes in day length and the endogenous phytohormone GA, respectively.…”
mentioning
confidence: 99%
“…ChIP was carried out as described (Liu et al, 2008) with some modifications. Briefly, about 250 mg of 1% formaldehyde-fixed young wild-type rice panicles (0.2-2 cm) was ground in liquid nitrogen and then sonicated to yield chromatin with DNA of less than 500 bp.…”
Section: Chip Analysismentioning
confidence: 99%